Improved Mechanical Properties and In-Vitro Degradation of Chitosan-Pristine Graphene Nanocomposites - Wajdi, Farid; Kusumaningtyas, Indraswari; Wijaya, Andi R.; Tontowi, Alva E. (International Journal of Integrated Engineering, 2021)
Studies over the use of pristine graphene as reinforcement for biopolymers are rarely found. In this study, we prepared biodegradable chitosan and pristine graphene nanocomposites films with a small amount of glycerol to enhance the bonding. The aim was to study the mechanical improvement and degradation rates of the nanocomposites material. Characterizations of the nanocomposites consist of a Fourier Transform Infrared (FTIR), Scanning Electron Microscopy (SEM), tensile and degradation testings. The results showed that glycerol improved graphene dispersion throughout the chitosan matrix due to the hydrogen bonding and electrostatic interactions between chitosan and pristine graphene. To some extent, pristine graphene improved the stiffness and tensile strength of chitosan that is emphasized by the glycerol. However, glycerol concentration should be increasing at an increased level of graphene in the chitosan matrix to prevent graphene agglomeration.